Rancang Bangun Aplikasi OPTIMUS+ pada PT. PLN (Persero) APJ Surabaya Barat - Tritita, Zulfa Ulinnuha; widodo, arifin puji; sutanto, teguh (Jurnal JSIKA, 2014)
Abstract : PLN area of West Surabaya (SBB) has a method called Operational Performance Improvement (OPI). OPI SBB currently run manually using paper and Microsoft Excel. In carrying out this activity, PLN SBB having some problems such as : the use of manual and EMI Survey still at risk for the resulting value of the indicator, the status of workplan activities are presented in Microsoft Excel is static and can not provide actual information, and the lack of information needed by managers to monitor the development of the initiative.To overcome some of these constraints, an application named OPTIMUS + is built. OPTIMUS+ has some functions : module EMI Surveys Online, Diagnose, Design, and Deliver all activities OPI. In addition to overcoming some of these problems, OPTIMUS + built in order to obtain the required output, such as recapitulation EMI Survey, EMI Survey graphs, workplan activity status information, and summary of workplan activities via the website and Short Message Service (SMS).OPTIMUS + can assist the implementation of the OPI to be maximal activity by discouraging risk of existing constraints and provide the advantage of ease in obtaining the required output.Keywords : Operational Performance Improvemance (OPI), OPTIMUS+, Website.Â